Community structure and biovolume size spectra of mesozooplankton in the Pearl River estuary. Issue 1 (2nd January 2018) - Ke, Zhixin; Tan, Yehui; Huang, Liangmin; Liu, Jiaxin; Liu, Huaxue
Abstract : The Pearl River estuary is the second largest estuary in China. This study reported the species composition and size structure of mesozooplankton in the upper and lower Pearl River estuary in the dry and wet seasons. The normalized biovolume size spectrum of mesozooplankton was constructed to analyze the trophic structure of the community. Copepods were the numerically predominant mesozooplankton group at all sampling stations. However, when converted into biovolume, medusae were dominant in the upper estuary in the dry season and Chaetognatha were dominant in the lower estuary in the wet season. There were apparent seasonal and spatial variations in the normalized biovolume size spectrum characteristics in the Pearl River estuary. In the dry season, the average fitted regression line of the normalized biovolume size spectrum had a slope of −1.02 in the upper estuary and −0.88 in the lower estuary. In the wet season, the average fitted regression line of the normalized biovolume size spectrum had a slope of −0.32 in the lower estuary, and no significant regression of the normalized biovolume size spectrum was found in the upper estuary. It is suggested that the mesozooplankton community was unstable in the upper estuary due to the strong freshwater perturbation in the wet season. The size diversity and normalized biovolume size spectrum slope indicated that the strength of top-down control and trophic efficiency was highest in the lower estuary in the wet season.